2017
DOI: 10.6002/ect.2015.0167
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Objectives: Organ transplant is an effective treat ment for patients with end-stage renal and hepatic failure. Increased use has introduced more emergency department admissions of infectious origin after transplant. Because infections usually manifest with simple complaints and fever, emer gency physicians need laboratory tests and radiologic imaging procedures to quickly detect the presence and source of infection. Our aim was to analyze fever-related emergency admissions of renal and hepatic graft recipients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
(12 reference statements)
0
1
0
Order By: Relevance
“…When cancer cells were active in reproduction, changes in the inflammatory microenvironment could lead to abnormal status in blood. 36, 37 When tumor progression or cell proliferation was active, not only CEA and CA19-9 and other indicators were abnormal, but RDW values beyond the normal range was also reflected in the blood test results, so patients with colorectal cancer were prone to both abnormal high values of tumor markers and RDW-CV in blood. Previous reports by Wei T, et al 17 had also found that RDW was significantly correlated with the levels of CEA and CA19-9 in gastric cancer.…”
Section: Discussionmentioning
confidence: 99%
“…When cancer cells were active in reproduction, changes in the inflammatory microenvironment could lead to abnormal status in blood. 36, 37 When tumor progression or cell proliferation was active, not only CEA and CA19-9 and other indicators were abnormal, but RDW values beyond the normal range was also reflected in the blood test results, so patients with colorectal cancer were prone to both abnormal high values of tumor markers and RDW-CV in blood. Previous reports by Wei T, et al 17 had also found that RDW was significantly correlated with the levels of CEA and CA19-9 in gastric cancer.…”
Section: Discussionmentioning
confidence: 99%